Functional and molecular differences between voltage-gated K+ channels of fast-spiking interneurons and pyramidal neurons of rat hippocampus - Martina, Marco; Schultz, Jobst-Hendrik; Ehmke, Heimo; Monyer, Hannah; Jonas, Peter (The journal of neuroscience, 1998)
We have examined gating and pharmacological characteristics of somatic K+ channels in fast-spiking interneurons and regularly spiking principal neurons of hippocampal slices. In nucleated patches isolated from basket cells of the dentate gyrus, a fast delayed rectifier K+ current component that was highly sensitive to tetraethylammonium (TEA) and 4-aminopyridine (4-AP) (half-maximal inhibitory concentrations <0.1 mm) predominated, contributing an average of 58% to the total K+ current in these cells. By contrast, in pyramidal neurons of the CA1 region a rapidly inactivating A-type K+ current component that was TEA-resistant prevailed, contributing 61% to the total K+current. Both types of neurons also showed small amounts of the K+ current component mainly found in the other type of neuron and, in addition, a slow delayed rectifier K+ current component with intermediate properties (slow inactivation, intermediate sensitivity to TEA). Single-cell RT-PCR analysis of mRNA revealed that Kv3 (Kv3.1, Kv3.2) subunit transcripts were expressed in almost all (89%) of the interneurons but only in 17% of the pyramidal neurons. In contrast, Kv4 (Kv4.2, Kv4.3) subunit mRNAs were present in 87% of pyramidal neurons but only in 55% of interneurons. Selective block of fast delayed rectifier K+ channels, presumably assembled from Kv3 subunits, by 4-AP reduced substantially the action potential frequency in interneurons. These results indicate that the differential expression of Kv3 and Kv4 subunits shapes the action potential phenotypes of principal neurons and interneurons in the cortex.